An assessment of hair cortisol among postpartum Brazilian mothers and infants from a high‐risk community in São Paulo: Intra‐individual stability and association in mother–infant dyads. Issue 7 (23rd August 2017) - Liu, Cindy H.; Fink, Günther; Brentani, Helena; Brentani, Alexandra
Abstract: This study examined maternal–infant synchrony of hair cortisol at 12 months after birth and the intra‐individual stability of maternal hair cortisol in the postpartum period. Participants were selected from an ongoing São Paulo birth cohort project, where families are considered to be "high‐risk" due to their chronic stress experiences, with the majority living in slums (favelas). Cortisol was collected through 3‐cm segments of hair samples, with values representing approximate levels of cortisol from 9 to 12 months for mothers and children and 6 to 12 months for mothers. Maternal and infant cortisol values reflecting chronic stress 9–12 months after birth were highly correlated ( r  = .61, p  < .001); earlier maternal cortisol levels (6–9 months) and child cortisol levels at 9–12 months ( r  = .51, p  < .001) were also correlated. Maternal cortisol values showed stability over time ( r  = .79, p  < .001). These maternal–infant correlations are high compared to the existing literature on hair cortisol in other mother–child dyads, suggesting stronger synchrony under high‐risk contexts where families are faced with challenging circumstances.